Ազգային տնտեսության մրցունակության և նորարարական համակարգի փոխկապվածությունը - Կ. Հ. Գրիգորյան; Դ. Ս. Գևորգյան (ՀՀ ԳԱԱ հրատ.)
На современном этапе глобализации и интеграции, когда границы между странами почти изчезают, роль конкуренции возрастает, в силу чего одним из важнейших факторов становится повышение тех качеств продуктов и услуг, что сделает их более конкурентоспособными. At the present stage of globalization and integration, when the borders between countries are almost disappearing, the role of competition is growing. That’s why the most important factors are the improvement of those qualities of products and services that will make them more competitive. Studies show that among the factors which shape competitiveness, one should choose those that provide a lasting effect, and such are innovations.
Keywords: H Social Sciences; Economic Theory